Augmenting self-guided virtual-reality exposure therapy for social anxiety with biofeedback: a randomised controlled trial - Premkumar, Preethi; Heym, Nadja; Myers, James A. C.; Formby, Phoebe; Battersby, Steven; Sumich, Alexander Luke; Brown, David Joseph (Frontiers in Psychiatry, 2024)
We (Premkumar et al., 2021) previously found that self-guided Virtual Reality Exposure Therapy (VRET) improved Public Speaking Anxiety (PSA) and reduced physiological arousal. Biofeedback also reduces physiological arousal from anxiety. If VRET reduces physiological arousal, giving continuous biofeedback could help socially anxious individuals to manage their anxiety. The present study aimed to understand whether biofeedback enhances the responsiveness of VRET. Seventy-two individuals with high self-reported social anxiety were randomly allocated to VRET-plus-biofeedback (n=38; 25 completers) or VRET-alone (n=35; 25 completers). Three hour-long VRET sessions were delivered over two consecutive weeks during which participants delivered a 20-minute public speech in front of a virtual audience. Participants in the VRET-plus-biofeedback group received biofeedback on heartrate and frontal alpha asymmetry (FAA) within the virtual environment during the speech and were asked to lower their arousal accordingly. Participants in both intervention groups completed psychometric assessments of social anxiety after each session and at one-month follow-up. PSA improved by the end of treatment and overall social anxiety improved at one-month follow-up across both groups. The VRET-plus-biofeedback group showed a steadier reduction in FAA than the VRET-alone group at just the first VRET session. The VRET+biofeedback group also produced a greater reduction in self-reported arousal. Thus, biofeedback can steady physiological arousal and lower perceived arousal momentarily. The benefits of self-guided VRET for social anxiety are sustained one month after therapy.